2017
DOI: 10.1002/ar.23547
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Integration of the Human Pelvis with Respect to Age and Sex

Abstract: Considerable research has shown that modern human pelvic dimensions, especially of the birth canal, are sexually dimorphic. Studies also suggest that females with younger ages-at-death have narrower canal dimensions than those who die at older ages, possibly due to continued independent growth of the pubis. A recent examination of this pattern argued that it is unlikely that these differences relate to mortality, but the source of the difference in pelvic dimensions with age remains unresolved. We use pelvic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 51 publications
(72 reference statements)
3
35
1
Order By: Relevance
“…In contrast, Betti et al () and Betti () showed that most os coxae shape variation reflects neutral evolutionary processes, but they did not rearticulate pelves in their sample and so could not examine obstetrical dimensions. These two sets of evolutionary model results are not necessarily in conflict, as most true pelvis dimensions are independent from BIB (Grabowski et al, ; Mallard et al, ). Larger BIBs do not guarantee that we would find most dimensions of the true pelvis larger in high latitude groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, Betti et al () and Betti () showed that most os coxae shape variation reflects neutral evolutionary processes, but they did not rearticulate pelves in their sample and so could not examine obstetrical dimensions. These two sets of evolutionary model results are not necessarily in conflict, as most true pelvis dimensions are independent from BIB (Grabowski et al, ; Mallard et al, ). Larger BIBs do not guarantee that we would find most dimensions of the true pelvis larger in high latitude groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of integration in the human pelvis (Grabowski, ; Grabowski & Roseman, ; Mallard et al, ) have shown that the dimensions of the three bones that comprise the os coxa are less independent than the os coxa as a whole; that is, the ischium, pubis, and ilium are more integrated individually than they are with each other. We may therefore conclude that the changes that occur between younger and older females in our sample are likely changes to the entire pelvis, and not necessarily driven by one region of the pelvis (cf.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations